Viewpoint : an introduction to travel, tourism, and hospitality - Starr, Nona S. (Prentice Hall, 2000)
Introduction. Places and people - destination geography. The North American aviation system. Airports - gateways to the world. The international experience. Travel by rail. Travel by road...